2022
DOI: 10.3390/ph15050591
|View full text |Cite
|
Sign up to set email alerts
|

Mangifera indica ‘Namdokmai’ Prevents Neuronal Cells from Amyloid Peptide Toxicity and Inhibits BACE-1 Activities in a Drosophila Model of Alzheimer’s Amyloidosis

Abstract: Alzheimer’s disease (AD) is a progressive neurological illness with few effective treatments. Thus, ameliorating the effects of AD using natural products has attracted global attention with promising efficacy and safety. In this study, ten tropical fruits including Ananas comosus ‘Phulae’, Ananas comosus ‘Pattavia’, Carica papaya ‘Khaekdum’, Carica papaya ‘Khaeknuan’, Durio zibethinus ‘Monthong’, Durio zibethinus ‘Chanee’, Psidium guajava ‘Kimju’, Psidium guajava ‘Keenok’, Mangifera indica ‘Kaew’ and Mangifera… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 58 publications
0
1
0
Order By: Relevance
“…indica ‘Namdokmai’ showed superior inhibition properties against AChE, BACE-1, and BChE. In the same study, anti-AD properties in the Drosophila model showed a significant reduction of BACE-1 in the brains of AD flies (6.03 U/mL) by 250 µg/mL of M. indica 'Namdokmai' extract ( Temviriyanukul et al, 2022 ). The present results indicated that Bao MPE showed higher inhibitory activity against enzymes involved in AD compared to the above-reported mango variety from Thailand.…”
Section: Discussionmentioning
confidence: 84%
See 2 more Smart Citations
“…indica ‘Namdokmai’ showed superior inhibition properties against AChE, BACE-1, and BChE. In the same study, anti-AD properties in the Drosophila model showed a significant reduction of BACE-1 in the brains of AD flies (6.03 U/mL) by 250 µg/mL of M. indica 'Namdokmai' extract ( Temviriyanukul et al, 2022 ). The present results indicated that Bao MPE showed higher inhibitory activity against enzymes involved in AD compared to the above-reported mango variety from Thailand.…”
Section: Discussionmentioning
confidence: 84%
“…Inhibition of cholinesterases (butyrylcholinesterase (BChE) and acetylcholinesterase (AChE)) that degrade neurotransmitters is crucial ( Moussa-Pacha et al, 2020 , Rajput et al, 2020a ). Phytochemicals from mango and its byproducts have been reported to have inhibitory potential for activities against neurotransmitters, acetylcholine, and degrading enzymes, AChE and BchE ( Temviriyanukul et al, 2022 ). However, compared to donepezil, which acts as a competitive cholinesterase inhibitor, the inhibitory potentials of mango peel extract were 2.6–44.0-fold higher, suggesting lower inhibitory strength against these enzymes.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…AChE: acetylcholinesterase; BChE: butyrylcholinesterase; BACE-1: β-secretase; DPP-IV: dipeptidyl peptidase-IV; IC 50 : half maximal inhibitory concentration; ND: not detected. Information on the positive controls was received from * Chupeerach et al, 2022 [ 20 ], $ Promyos et al, 2020 [ 21 ], and # Temviriyanukul et al, 2022 [ 22 ].…”
Section: Figurementioning
confidence: 99%